O09-2 Leading indicators: applying the institute of work and health (IWH) organisational performance metric (OPM) to british columbia (BC), canada. (1st September 2016) - Marino, Suhail Carina; McLeod, Christopher; Tamburic, Lillian; Quirke, William; Koehoorn, Mieke; Amick, Benjamin
Abstract : Objectives: To validate a set of leading health and safety indicators that organisations can use to assess and improve their health and safety performance in the province of British Columbia. This project evaluated the OPM, an 8-question health and safety practice questionnaire developed by IWH for use as an OHS leading indicator tool in BC and how well it correlated with retrospective and current claim rates of participating firms. Method: The IWH OPM was used in two sectors – residential long-term care and the food processing and manufacturing. Firm contact information was provided by safety associations in each sector. Firm responses were collected via an online survey (2 surveys per firm, with management and labour respondents). Survey psychometric properties were evaluated. Item-to-scale correlation, factor analysis and Cronbach's alpha assessment were conducted. Results: Respective response rate for the long-term care and Food and Manufacturing Sector were 37% and 11%. Each of the eight questions showed variability in OHS practices across firms, with firms reporting doing least well on involving their employees in OHS decision-making (50% of the sample indicating need for improvement). 65% of the sample indicated they were doing well on most items, and 35% indicated need for improvement in 4 or more areas. Factor analysis showed that the OPM items capture a single measure of occupational health and safety performance, while Cronbach's Alpha indicate that all items contribute information to the scale. Overall there were no differences in average assessment of scale items by management or labour or by those with OHS responsibility versus none. Conclusions: The IWH OPM appears to be a valid tool for measuring OHS outcomes in BC. It can be used as a leading indicator scale to help reduce occupational injury; however, efforts need to be taken to improve firm willingness to answer the survey.